Part 2: Monitoring training status with player-tracking technology. Still on the road to Rome - Increasing coach "buy-in" with good data visualisation - Lacome, M.; Simpson, B. M.; Buchheit, M. (ASPETAR Sports Medicine Journal, 2018)
As we have seen in part 1, we believe that practitioners with a clear vision of the framework to develop and improve the models used to analyse training loads will be able to gain better insight into players` fitness, readiness to perform and fatigue.